2022
DOI: 10.1097/crd.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Mavacamten: A Novel Disease-Specific Treatment for Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is characterized by an abnormal thickening of the myocardium, leading to left ventricular outflow tract obstruction. Current treatments for HCM include non–disease-specific medications such as beta blockers or invasive interventions. Mavacamten has been studied for its effects on adenosine triphosphatase, myocardial-specific sarcomeric proteins, and myocardial tissue calcium sensitivity. Given these properties, mavacamten could be used as a disease-specific treatment for HCM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been reported that the IC 50 values of Mavacamten in the bovine, human, and rabbit system are 490 nM, 711 nM, and 2140 nM, respectively, indicating a 4-fold selectivity for myocardial myosin [ 176 178 ]. Mavakamten is found to reduce contractility through decreasing the activity of adenosine triphosphatase in the heavy chain of myocardial myosin [ 179 ]. Long-term administration results in the inhibition of the development of myocardial cell disorders, myocardial hypertrophy, and myocardial fibrosis, and attenuates the gene expression of profibrotic and hypertrophic in mice featuring heterozygous human mutations in the chain of myosin heavy [ 176 ].…”
Section: Other Drugsmentioning
confidence: 99%
“…It has been reported that the IC 50 values of Mavacamten in the bovine, human, and rabbit system are 490 nM, 711 nM, and 2140 nM, respectively, indicating a 4-fold selectivity for myocardial myosin [ 176 178 ]. Mavakamten is found to reduce contractility through decreasing the activity of adenosine triphosphatase in the heavy chain of myocardial myosin [ 179 ]. Long-term administration results in the inhibition of the development of myocardial cell disorders, myocardial hypertrophy, and myocardial fibrosis, and attenuates the gene expression of profibrotic and hypertrophic in mice featuring heterozygous human mutations in the chain of myosin heavy [ 176 ].…”
Section: Other Drugsmentioning
confidence: 99%